Reflections on how far Brazil can go with Financial Education in Basic Education - Campos, Celso Ribeiro; Perin, Andréa Pavan; Pita, Ana Paula Gonçalves (Educação Matemática Debate, 2024)
Some international assessment on financial literacy showed Brazil’s low score in comparison to other countries. Although Financial Education began in Brazil in 2010 as a National Strategy, it was in 2018 that a new curriculum was established for Basic Education addressing actions for the development of financial literacy. The objective of the study was to investigate some characteristics of countries that performed better in financial literacy to analyze what Brazil should seek to achieve higher grades. The research is quantitative and based on documental analysis. Study results showed that some important features are outside the educational system and would restrict the achievements that Brazil can pursue.